Hand strength and dexterity in patients with Prader–Willi syndrome: a pilot intervention study. Issue 11 (November 2018) - Hsu, Wan-Ling; Chiu, Valeria Jia-Yi; Chang, Wei-Hsiu; Lin, Mei-Chun; Wei, Jang-Ting; Tzeng, I-Shiang
Objective: The study aim was to examine the hand function (hand strength and dexterity) and intervention effects of training in adults with Prader–Willi syndrome (PWS). Methods: Six adults with PWS (two females; mean age 26.14 years) underwent hand muscle strength and dexterity training for 3 months (2 hours per week). The following hand function tests were performed pre- and post-intervention: (1) hand grip, lateral pinch, and tip pinch hand strength tests, (2) the Box and Block test (BBT) for gross manual dexterity and (3) the Purdue Pegboard test for finger dexterity. Results: Before treatment, all subjects showed lower hand grip, lateral pinch, tip pinch strength, and poorer manual/finger dexterity relative to healthy adults. After training, hand function scores improved on many test items, but only the left hand tip pinch and the right hand BBT performance showed significant improvements. Conclusions: All subjects showed lower hand strength and poorer manual/finger dexterity compared with healthy adults; this should be considered during physical training programs. Owing to limitations in the intervention intensity and possible subject behavioral deficits, further research is needed to clarify the effects of this intervention on hand function in PWS patients.